TEST OF TIMBAL (Pb) CONTENT IN THE URINE OF CLEANING STAFF AT THE WASTE DISPOSAL PLACE BASED ON AGE BY METHODS OF ATOMIC ABSORPTION SPECTROFOTOMETER - Wulandari, Retno; Hanum , Galuh Ratmana (Journal for Technology and Science, 2024)
A pile of garbage produced by an increase in the needs of the community and can pollute the environment. Lead (Pb) is a heavy metal that is toxic from the air, which can have harmful effects for health. Cadmium (cd) is one of the metal contained in cigarettes tobacco that has a high toxicity properties. Lead (Pb) and Cadmium (Cd) can cause damage to the kidney system. Then the rest of the metabolism is excreted through the urine. This research is for to determine the level of lead (Pb) and cadmium (Cd) and relation between Lead (Pb) and Cadmium (Cd) in urine with the age of the janitor in the garbage dump. In this research, it uses the type of experimental research with 20 urine samples and conducted in March 2021 at the Laboratory of TLM Faculty of Health Sciences Muhhamdiyah Sidoarjo University and UIN Maulana Malik Ibrahim Malang. Data analysis methods use pearson correlation statistics. The results are measured using the AAS method for Timbal (Pb) below the limit 0.15 mg/L and Cadmium (Cd) below the limit 0.01 mg/L. The pearson correlation test of Timbal (Pb) and Cadmium (Cd )is sig. < 0.05, so Ha accepted and it said there was a relation between heavy metals in urine and age.